Up Front Journal Februrary 1976 (1976)
The February 1976 California Journal "Up Front" column highlights Governor Jerry Brown's unconventional style, including an austere holiday party for the Capitol press corps and the creation of the new Office of Appropriate Technology to promote environmentally aligned policies. It also recounts how Brown nearly learned of his press secretary Bill Stall's resignation through newspaper reports after Stall accepted a job with the Los Angeles Times. The decision of Assemblywoman Pauline Davis not to seek reelection raises concerns about a potential decline in the number of women legislators. The column mentions Jane Tolmach, former mayor of Oxnard, as a promising Assembly candidate if a vacancy opens. he page also includes the issue's table of contents, outlining articles on public dissatisfaction with government, legislative politics, judicial diversity, environmental law, and California's budget surplus.